2009
DOI: 10.1007/s11816-009-0103-x
|View full text |Cite
|
Sign up to set email alerts
|

Development of a CMS-specific marker based on chloroplast-derived mitochondrial sequence in pepper

Abstract: Molecular markers developed from the flanking sequences of two cytoplasmic male sterility (CMS)-associated genes, orf456 and watp6-2, have been used for marker-assisted selection of CMS in pepper. However, in practice, the presence of orf456 and watp6-2 at substoichiometric levels even in maintainer lines hampers reliable selection of plants containing the CMS gene. In this study, we developed a novel CMS-specific molecular marker, accD-U, for reliable determination of CMS lines in pepper, and used the newly a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 31 publications
2
10
0
3
Order By: Relevance
“…1 and Table 5). This result is consistent with our recent finding that atp6-2 discriminates CMS lines more specifically than orf456 (Jo et al 2009b), but contrasts with previous results that orf456 alone can induce male sterility (Kim et al 2007). The presence of orf456 in several maintainer lines and commercial cultivars indicates that factors other than orf456 may be required to induce CMS in peppers.…”
Section: Haplotype Analysis Of Cytoplasmic Cms-associated Markers In supporting
confidence: 87%
“…1 and Table 5). This result is consistent with our recent finding that atp6-2 discriminates CMS lines more specifically than orf456 (Jo et al 2009b), but contrasts with previous results that orf456 alone can induce male sterility (Kim et al 2007). The presence of orf456 in several maintainer lines and commercial cultivars indicates that factors other than orf456 may be required to induce CMS in peppers.…”
Section: Haplotype Analysis Of Cytoplasmic Cms-associated Markers In supporting
confidence: 87%
“…The CRF-SCAR marker results in our study showed that the fertile and sterile plants segregated in a 3:1 ratio (Table 3), which suggests that the Rf gene in our CMS material was a major Rf gene (Peterson, 1958;Novak et al, 1971). Several CMS markers have been reported (Kim and Kim, 2005;Jo et al, 2009), but the CMS-SCAR 130 marker (Ji et al, 2014) has been suggested to be more reliable than others (Dhaliwal and Jindal, 2014). In our work, the 130 bp CMS-SCAR 130 DNA marker differentiated fertile individuals in line YBM12-A, and in the F 1 and F 2 hybrids.…”
Section: Discussionmentioning
confidence: 45%
“…Two CMS-specific SCAR markers (coxII and atp6) were developed to distinguish normal (N) from sterile (S) cytoplasm using polymerase chain reaction (PCR) analysis. Other molecular markers, such as accD-U7 (Jo et al, 2009) and orf456 (Kim et al, 2007), have been used to speed up CMS selection and application, and to improve breeding outcomes. However, a single molecular marker for determining S-cytoplasm has not yet been identified as reliable or correct.…”
Section: Introductionmentioning
confidence: 99%
“…Several CMS-specific DNA markers have been developed (Kim and Kim, 2005). Two SCAR markers based on mitochondrial sequence were reported by Kim and Kim (2006) and Jo et al (2009), respectively. However, their application is limited because slight PCR amplification of these markers can occasionally occur even in pepper maintainer lines (Min, 2009).…”
Section: Introductionmentioning
confidence: 99%